Employee Payment Information System Design at PT Tamanaco - Moch. Aji Bagus Firmansyah; Uce Indahyanti (Procedia of Engineering and Life Science, 2022)
This research is motivated by the existence of problems in the scope of the payroll information system. Problems in the form of inaccuracies in the calculation of employee salaries, and invalidity in salary. The purpose of this study is to build a system that aims to provide convenience and accuracy in managing the amount of employee salaries, as well as providing convenience in generating reports related to payroll at PT. Tamanaco. The method used in this research is data collection using literature study, interviews and system development with the waterfall method. The results of this study indicate that all menus and features in the system are running well and the system can process salary data and print salary slips correctly. This research can contribute to the company in the hope of providing convenience in producing reports related to payroll, and is expected to provide additional knowledge and can be a reference material in the field of technology, especially the field of Information Technology studies.